Fusarium subtropicale, sp. nov., a novel nivalenol mycotoxin–producing species isolated from barley (Hordeum vulgare) in Brazil and sister to F. praegraminearum. (3rd September 2018) - Pereira, Carolina B.; Ward, Todd J.; Tessmann, Dauri J.; Del Ponte, Emerson M.; Laraba, Imane; Vaughan, Martha M.; McCormick, Susan P.; Busman, Mark; Kelly, Amy; Proctor, Robert H.; O'Donnell, Kerry
ABSTRACT: Surveys were conducted in commercial wheat and barley fields in the south central production regions of state of Paraná, Brazil, from 2011 to 2015. Spikes displaying visible Fusarium head blight symptoms were collected and the pathogen isolated from the tissues. The 754 Fusarium isolates recovered were identified by a high-throughput multilocus genotyping assay (MLGT) designed to identify trichothecene toxin–producing fusaria (i.e., formerly B-clade, but referred to here as F. sambucinum species complex lineage 1 [FSAMSC-1]) together with sequencing a portion of the translation elongation factor 1-α ( TEF1 ) gene. One strain was discovered that appeared to be closely related to but phylogenetically distinct from F. praegraminearum based on the relatively low 97.7% TEF1 identity and positive genotype obtained with one of the two F. praegraminearum species–specific MLGT probes. Molecular phylogenetic analyses of a 10-gene data set resolved this novel FSAMSC-1 species and F. praegraminearum as sisters. Formally described herein as F. subtropicale, it is phenotypically distinct from the 22 other FSAMSC-1 species in that it produces mostly 1–3-septate macroconidia. Whole-genome sequence data were used to predict its potential to produce mycotoxins. Chemical analyses confirmed that F. subtropicale could produce the mycotoxins 4, 15-diacetylnivalenol, butenolide, culmorin, and fusarin C in vitro, and the pathogenicity experiment revealed that F. subtropicale could infect but not spread in susceptible hard red spring wheat cultivar "Norm."